Pedagogias de gênero em narrativas sobre transmasculinidades - Pamplona, Renata Silva (2017)
This research aims to analyze aspects of transmasculinities from the autobiographical accounts of four Brazilian men. The proposed objective is based on the understanding that transmasculinities, when compared to other sexual and gender minorities, have less political visibility. However, in Brazilian society, in recent years, this visibility has gradually been constituted by a certain activism exercised by transmen. The problem raised is to analyze through the accounts of four transsexual men how these individuals have constructed possible tools to confront the hegemonic matrix of masculinities. The hypothesis is that transmasculinities may constitute an inventive category of life potentials and an exercise capable of subverting the sex/gender system through the production of multiple expressions of masculinities. We understand that knowledge and pedagogical practices (school and non-school) are intimately involved in the processes of the production of subjectivities and the power relations that regulate people's bodies. They make it appear that some normative identities are naturally constitutive of the subjects and not strategically produced and taught by the normalization exercises of behaviors and bodies. As a theoretical option, this study draws on some concepts of post-structuralist studies and gay and feminist studies, centered predominantly on readings of Michel Foucault, Gilles Deleuze, Félix Guattari, Beatriz Preciado and Judith Butler. In the first instance, our methodological procedure consists of the presentation of the object of study and the problematization surrounding the concepts of transsexuality and transmasculinity. Subsequently, we analyze the literary accounts of three trans men: John W. Nery, Jô Lessa and Anderson Herzer. Finally, we offer an analysis of twenty-one letters written by Dom, an anonymous transhuman who relates his life experiences and the territories traced in the experience of his transmasculinity. Having examined the wealth of these distinct productions from the subjectivities of the trans male universe, it is striking to note the extent to which they seek to multiply the possibilities of living out masculinities. However, the risk of subjection and abjection is permanent when one lives on the frontier of dichotomous genres, sometimes leading to entrapment within the staging of the heterocentric system. Thus, the process of deconstructing hegemonic masculinity for trans men is a continuous task in becoming.